Low-Dose Acetylsalicylic Acid Use and the Risk of Upper Gastrointestinal Bleeding: A Meta-Analysis of Randomized Clinical Trials and Observational Studies - Vera E Valkhoff; Miriam CJM Sturkenboom; Catherine Hill; Sander Veldhuyzen van Zanten; Ernst J Kuipers (Canadian Journal of Gastroenterology)
BACKGROUND: Low-dose acetylsalicylic acid (LDA, 75 mg/day to 325 mg/day) is recommended for primary and secondary prevention of cardiovascular events, but has been linked to an increased risk of upper gastrointestinal bleeding (UGIB).